A CORPUS-BASED STUDY ON THE TECHNICAL VOCABULARY OF ISLAMIC RELIGIOUS STUDIES - Simbuka, Srifani; Abdul Hamied, Fuad; Sundayana, Wachyu; Kwary, Deny A. (TEFLIN Journal, 2019)
This paper charts the construction of a technical vocabulary list called the Islamic Religious Studies Textbooks Vocabulary (IRSTV) which was developed from the Corpus of Islamic religious studies textbooks (CIRST) in an Indonesian Islamic State Institute (IISI). The study is aimed to meet the need of first-year English language learners studying in Indonesian Islamic tertiary education. The IRSTV list contains selected word types extracted from five major sub-disciplines of Islamic Religious Studies (IRS), i.e. the science of Qur'an, the science of Hadiths, Islamic law and jurisprudence, Islamic philosophy and theology, and Islamic mysticism theology, taught in most Indonesian Islamic universities and colleges. The quantitative analysis of frequency, range and keyness score ranking was conducted and aided by Corpus analysis software i.e. Antwordprof and Antconc keyword tool. A final triangulated ranking of these three criteria was conducted to produce a more balanced technical vocabulary list resulting in 262 word types or 239 lemmas of English words that are needed to be learned by English as Foreign Language (EFL) students of Indonesian Islamic universities, state institutes and colleges.